2020
DOI: 10.1161/hypertensionaha.119.14307
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Arterial Stiffness With Cognitive Performance, and the Role of Microvascular Dysfunction

Abstract: The mechanisms underlying cognitive impairment are incompletely understood but may include arterial stiffness and microvascular dysfunction. In the population-based Maastricht Study, we investigated the association between arterial stiffness and cognitive performance, and whether any such association was mediated by microvascular dysfunction. We included cross-sectional data of 2544 participants (age, 59.7 years; 51.0% men; 26.0% type 2 diabetes mellitus). We used carotid-femoral pulse wave velocity and caroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 39 publications
0
25
1
1
Order By: Relevance
“…In a recent cross‐sectional study of 2,544 patients, aortic stiffness as measured by carotid femoral pulse wave velocity was associated with cognitive dysfunction. Data showed that 16% of the effect of aortic stiffness on cognitive dysfunction was explained by microvascular dysfunction, as measured by magnetic resonance imaging, flicker light‐induced retinal arteriolar and venular dilation response, albuminuria, and plasma biomarkers of microvascular dysfunction 111 . Similar studies have shown an association between large vessel stiffness and microvascular dysfunction in the retina and kidney 112,113 .…”
Section: Microvascular Dysfunction In Distant Organsmentioning
confidence: 86%
“…In a recent cross‐sectional study of 2,544 patients, aortic stiffness as measured by carotid femoral pulse wave velocity was associated with cognitive dysfunction. Data showed that 16% of the effect of aortic stiffness on cognitive dysfunction was explained by microvascular dysfunction, as measured by magnetic resonance imaging, flicker light‐induced retinal arteriolar and venular dilation response, albuminuria, and plasma biomarkers of microvascular dysfunction 111 . Similar studies have shown an association between large vessel stiffness and microvascular dysfunction in the retina and kidney 112,113 .…”
Section: Microvascular Dysfunction In Distant Organsmentioning
confidence: 86%
“…Since subclinical atherosclerosis interfere with future clinical CVD and physical/cognitive functioning, the potential effect of modifiable health behaviors on subclinical atherosclerosis in midlife and early postmenopausal women warrants further investigation, as it may be a critical window of opportunity for prevention [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…However, epidemiologic data clearly suggest that the potential impact of vascular risk factors on dementia may not be entirely through easily measurable vascular disease (such as stroke or small vessel disease or silent brain infarcts), or at least as limited by current technology. Microvascular dysfunction, measured using magnetic resonance imaging (MRI) as well as biomarkers of microvascular disease, only accounted for 16.2% of the effect of aortic stiffness on cognitive function, 20 white matter hyperintensities (WMH) only partially mediated the effect of hypertension on cognition, 21 and mediation analyses of other vascular risk factors have not found a clear imaging feature explaining the relationship between risk factor and cognition 22 . As technology and biomarkers of downstream vascular changes of these risk factors improves, more will be understood about the full range of mechanisms at play relating to these risk factors.…”
Section: Current State Of Knowledgementioning
confidence: 99%
“…The CAIDE (Cardiovascular Risk Factors, Aging and Dementia study) risk score strongly predicted late‐life dementia, when considered in midlife, 29 and had an area under the curve of 0.74 for dementia prediction in a study of Finnish twins 30 . Life course is especially relevant because risk factors appear to be most strongly associated with adverse cognitive outcomes when considered in middle age, or perhaps even earlier: mid‐life exposure (45 to 64 years) to hypertension, smoking, and diabetes has a greater impact on dementia risk than similar risk factors in late‐life (>65 years), 17‐35 with a near‐doubling of dementia risk from midlife diabetes (hazard ratio [HR] 1.77, 95% confidence interval [CI] 1.53 to 2.04), a > 40% increased risk of dementia for midlife smokers (HR 1.41, 95% CI 1.23 to 1.61), and a similarly elevated risk for individuals with hypertension in middle age (HR 1.39, 95% CI 1.22 to 1.59), in the ARIC study, 17 with even higher estimates for more pronounced increases in blood pressure (HR 4.8, 95% CI 2.0 to 11.0 in the Honolulu Heart Program for midlife blood pressure 160 mm Hg and higher and risk of dementia) 36 …”
Section: Current State Of Knowledgementioning
confidence: 99%